Legal Features and Aspects of Medical Tourism: Legal Aspects of Medical Tourism - Abualhasani, Nazanin (Bioethics and Health Law Journal (BHL), 2021)
Background and Aim: The high cost of health care and long waiting time of the patients caused the creation of the motivation that patients, especially from the developed countries, receive these services in other countries. On the other hand, also in developing countries, factors such as globalization and liberalization of trade in health services led the way for the rapid growth of medical tourism. However, this industry is facing several challenges, among the most important, legal aspects can be noted. Since little research has been done in this regard, this study aims to evaluate the legal aspects related to medical tourism. Materials and Methods: This study is a review article on the legal issues of medical tourism. To collect information on the legal issues of medical tourism, databases, SID and PubMed, Google Scholar were examined using the keywords "medical tourism", "health tourism" and "legal aspects" and about 47 related articles were found, after studying the titles and abstracts of the articles found, 23 subjects which were associated with the research topic, were studied. Then the results obtained were analyzed. Ethical Considerations: Honesty and integrity were taken into consideration in searching, analyzing, and reporting the texts. Findings: According to the results of the study, the medical tourism industry is growing, but there are challenges related to the legal aspects of medical tourism include the areas of access to services, medical errors, health insurances, licensing, and regulatory approvals of centers, medical operations, and medical technologies. Conclusion: Medical Tourism legal challenges should be taken into consideration by policymakers and trustee institutions in this industry, as according to the globalization of these challenges, trying to eliminate them is necessary, which by turning threats into opportunities, facilitates the attraction process of foreign patients. *Corresponding Author: Nazanin Abualhasani; Email: na_abolhassani@yahoo.com; ORCID: https://orcid.org/0000-0002-3616-3595 Please cite this article as: Abualhasani N. Legal Features and Aspects of Medical Tourism. Bioeth Health Law J. 2021; 1:1-6: (e6). http://doi.org/10.22037/bhl.v1i1.38131